Pembangunan Sistem Point of Sale Yang Terintegrasi Dalam Setiap Cabang Outlet (Studi Kasus : 30 Derajat Street Food Tulungagung) - Yuni Panca Wati; Denny Sagita Rusdianto; Adam Hendra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
30 Derajat Street Food has been a culinary business which already has widely spread branches in Tulungagung. However this business still uses a manual book to take down every transaction such as sales recapitulation and every single expense. As the result, to take down the financial recapitulation will surely take a long time. Accordingly, Point of sale website based built up which is then directly integrated to every outlet branch. Development of this system uses Software Development Life Cycle Software with Waterfall model. The result software engineering shows of accounting needs, there were 37 functional and non-functional requirements, compatibility. This system is designed and is implemented by using an object oriented approach uses the Codeigniter framework with the MVC model (Model, View, Controller). Dealing with the test used, this research applies some tests covering white box method for the unit test, basis path testing for the technique, black box for validation test with 48 cases with 100% success and the last tool sortsite for compatibility test which is succesfully accessed by the six different browsers.